Measuring financial performances stated-owned bankig industry in Indonesia using risk based bank rating - Ahyar Arrifa'i, Miftahul; Mardawiyah Daryanto, Wiwiek (The Indonesian Journal of Business Administration, 2018)
Abstract. The measurement of financial performance is becoming increasingly important due to the Economic crisis of 1997/1998 hit Asia country and slower economic growth in Indonesia since 2012. The regulation of Financial Service Authority (OJK) provides the mandatory of Measuring Health Level Assessment System of Banking Industries in Indonesia by Circular Letter SE No.14/SEOJK.03/2017. This study has a purpose to measure financial performances of state-owned banks and one private bank Indonesia in 5 years covered (2012– 2016), Risk Based Bank Rating (RBBR) is the method framework that used to measure the financial performance such as Risk Profile Factor, Good Corporate Governance, Earning and Capital. The result of the study shows that over the last five years, the financial performance achieved 5 banks seem increasing of non-performing loan and impact on declining ROA performances even though the measurement was validated as healthy predicate respectively based on OJK standard rating. Research findings is getting strong by multivariate regression result shows that there is significant indication that NPL that affected to ROA performances. As recommendation, this research suggests that all the task that need as the credit analyst must be handed to professional employee according to 5c of credit concept to improve the effectiveness credit analyst approving credit loan. By improving quality credit analyst, DuPont analysis is conducted to show how the effectiveness given towards ROA Performance.Key words: Financial performance, Risk Based Bank Rating, Risk Profile Factor, Earning, Good Corporate Governance, Capital State-owned-Company banks.